IMPLEMENTATION OF SELF-COMPASSION-BASED CAREER LEARNING MODEL TO ADDRESS CAREER ANXIETY IN ADOLESCENTS - Nor Azlinda (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
This research aims to develop a self-compassion-based career learning model to overcome career anxiety in adolescents. The concept of self-compassion is understood as the ability to understand, accept, and feel sorry for oneself in the face of failure, difficulties, and pressure in a career context. This research combines supporting theories that support the relevance of self-compassion in developing career learning models. The proposed learning model includes a description of the model, model components, and integration of the concept of self-compassion. This model is designed to help teens better understand and manage their career anxieties. The components of the model include techniques for developing self-compassion, strengthening problem-solving skills, and introducing the world of work through a supportive approach. Implementing the model in the school environment requires effective strategies, such as training for teachers and counselors, providing the necessary resources, and support from the school and parents. Contextual factors, such as school culture, social support, and educational policies, also need to be considered in implementing this model. The research results show that developing a self-compassion-based career learning model can help teenagers reduce their career anxiety and improve their overall psychological well-being. By implementing this model, it is hoped that teenagers can better prepare themselves to face future career challenges